EFFECT OF SALINITY, TEMPERATURE, AND FOOD VALUE OF FOUR MICROALGAE TO OYSTER, Crassostrea iredalei LARVAL GROWTH - Achmad Sudradjat (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Published accounts of Crassostrea iredalei are only of its distribution in the Philippines. In Indonesia, this species is known to occur on the coast of South Sulawesi as well as in Banten. The purposes of the present studies were to investigate effect of salinity, temperature and food value of four microalgae to C. iredalei larval growth. Fine filtration of water was carried out using Sartorius capsule filter cartridge (1.2 ìm and 0.2 ìm) and sterilization was achieved by passing the water through an ultraviolet light unit. Low-salinity water was prepared by diluting filtered seawater with distilled water. High-salinity water was made by adding synthetic sea salts. All cultures were kept in constant temperature baths. Experiments of 8-days (for temperature and salinity trials) and 10-days (for diet trial) duration were duplicated in 500 mL glass beakers with larval density of 104 per liter. Seawater was changed every 48 h. The algae, Isochrysis galbana, I. galbana clone T-ISO, and Pavlova lutheri were added to the glass beakers at a rate of 100 cells/ìL; cell density of Chaetoceros calsitrans was 250 cells/ìl at the start of the experiment and after every water change. Using thermostat chambers, 5 temperatures were tested, ranging from 14o to 34o in 5 steps. Four salinities were used, they ranged from 10 to 35‰ in 5‰ steps. For environmental condition trial, I. galbana as food was used. In diet trials, 4 species of algae were tested e.g. I. galbana, I. galbana T-ISO, P. lutheri, C. calcitrans and a mixture of algae, T-ISO/C. calcitrans. The optimum salinity range for growth of larvae was recorded at 20‰—30‰ at which the mean shell length was 85.1—87.7 ìm. The highest survival rate was recorded at salinity of 25‰—30‰, it was 91.6%—92.7%. There were significant differences in larval growth between temperature treatments. The optimum temperature for larval growth was at 24°C—29°C, with survival rate of 91.6%—93.0%. P. lutheri and I. galbana proved to be of equal value as diet for larval growth, with survival rates of 89.4%—90.6%. The best algal food was I. galbana clone T-ISO, which resulted in mean shell length 107.7 ìm and survival rate 86.7%.